Phytochemical Screening of Gogauke Bio Oil as an Excellent Bio-Product for Natural Resource Management Solutions in Papua - Mingle A Pistanty; Sarima; Wahyu Purwanjani (Jurnal Penelitian Pendidikan IPA, 2025)
The Potential of Papua's Gogauke for Bio-Excellent Superior Products Papua possesses abundant biodiversity, and the Provincial Government is committed to green growth and sustainable natural resource management. Based on Special Autonomy, the rights of indigenous communities to protect the forests are also recognized. Local plants are often overlooked, despite having great potential. One such plant is Gogauke (Centella asiatica), traditionally used by Papuans as medicine. This plant is known to have various benefits, such as anti-inflammatory properties, wound healing, and pain relief. The objective of this research is to determine the potential of gogauke as a natural raw material for the superior product "Bio-Excellent" through phytochemical screening of the bio-oil produced. Using an experimental method, the study shows that Gogauke bio-oil has very strong potential for development. Phytochemical tests prove the product is rich in secondary metabolite compounds, including Alkaloids, Flavonoids, Triterpenoids, Tannins, Phenols, Steroids, and Glycosides. This combination of compounds provides a scientific basis for broad biological activities (antioxidant, anti-inflammatory, and antifungal). Furthermore, physical parameters (water content 9.8%, yield 44.14%) and microbiological test results (TBC and YMK) indicate that the bio-oil is safe and stable, meeting the BPOM standards for natural medicinal products. Conclusion: Gogauke bio-oil has a superior biochemical profile and high market potential, making it a promising "Bio-Excellent" product derived from Papua's sustainably managed natural resources.